2021
DOI: 10.1182/blood.2020006765
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the MAPK pathway mediates resistance to PI3K inhibitors in chronic lymphocytic leukemia

Abstract: Inhibitors of Bruton's tyrosine kinase (BTKi) and phosphatidylinositol 3-kinase delta (PI3Kδi) that target the B cell receptor (BCR) signaling pathway have revolutionized the treatment of chronic lymphocytic leukemia (CLL). While mutations associated with resistance to BTK inhibitors have been identified, limited data are available on mechanisms of resistance to PI3Kδi. Here we present findings from longitudinal whole-exome sequencing of multiply relapsed CLL patients (Ncases=28) enrolled in PI3Ki trials. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Most of the patients included in this study had never received treatment for CLL (10/13 patients; ‘CLL’ patients listed in Table 2 ). To investigate whether treatment status affected sensitivity to MEK/Bcl‐2 inhibition, we performed the same analysis on a cohort of CLL patients that were treated with the PI3K inhibitor idelalisib as first line or following chemoimmunotherapy (‘JB’ patients listed in Table 2 ) [ 8 ]. Drug sensitivity screens were performed on the patients’ CLL cells collected prior to start of treatment with idelalisib ( n = 6), while the patients were responding to idelalisib ( n = 7), and when the patients had developed resistance to idelalisib ( n = 4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the patients included in this study had never received treatment for CLL (10/13 patients; ‘CLL’ patients listed in Table 2 ). To investigate whether treatment status affected sensitivity to MEK/Bcl‐2 inhibition, we performed the same analysis on a cohort of CLL patients that were treated with the PI3K inhibitor idelalisib as first line or following chemoimmunotherapy (‘JB’ patients listed in Table 2 ) [ 8 ]. Drug sensitivity screens were performed on the patients’ CLL cells collected prior to start of treatment with idelalisib ( n = 6), while the patients were responding to idelalisib ( n = 7), and when the patients had developed resistance to idelalisib ( n = 4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such mutations are therefore unlikely to fully explain the sensitivity to MEK inhibition observed here. Furthermore, it has been shown that activation of ERK is associated with resistance to idelalisib in CLL irrespective of mutations in the MAPK pathway [ 8 ]. To investigate underlying mechanisms of the disease‐specific drug sensitivities observed here, we performed high‐throughput profiling of 31 intracellular proteins, including members of the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CLL, primary GoF, driver mutations are found in components of not only the NF-κB but also of the RAS-MAPK pathway, as depicted in Figure 3 ( 112 , 113 , 120 ). The very recent report demonstrating that resistance mutations to inhibitors of p110δ selectively affects the MAPK pathway in CLL patients is highly interesting ( 121 ). It shows that also this arm of the BCR pathway can be affected by resistance mutations ( Figure 1 ), although they never appear after BTKi treatment.…”
Section: Recurrent Primary Mutations In B Cell Malignancies Responding To Btkimentioning
confidence: 99%
“…Regarding the new targeted therapies (Table 1), mutations in the MAPK pathway are mediators of primary resistance to PI3K inhibitors [61]. Furthermore, activation of ERK1/2 has been associated with ibrutinib resistance [102], raising the possibility that patients with mutations in this pathway might have reduced sensitivity to ibrutinib.…”
Section: Recurrent Mutations and Alterations In Mapk Pathwaymentioning
confidence: 99%